Social capital-based financial literacy to improve business performance: a narrative review - Made Ary Meitriana; Ni Nyoman Yuliarmi; Made Suyana Utama; Anak Agung Istri Ngurah Marhaeni (International Journal on Social Science, Economics and Art, 2022)
MSMEs typically do not comprehend the financial products provided by financial institutions. This harms corporate performance. This study's objective is to examine the role of financial literacy based on social capital, the function of financial literacy in the business performance of MSMEs, and the impact of social capital in enhancing business performance. The Scale guides the writing of narrative reviews for the Assessment of Narrative Review Articles. The article's notability is determined independently by examining the title and abstract. Articles were searched using the databases of Google Scholars, Science Direct, Emerald, Taylor Francis, and SciFinder with the keywords' financial literacy', 'social capital,' 'business performance,' 'MSMEs,' 'microenterprises,' 'finance,' and 'civic organizations. The results show that high financial iterations both help entrepreneurs in making financial decisions well and have a positive effect on business performance. If MSME owners are 'blind' to the organization's finances, insufficient financial knowledge will have implications for a decrease in the ability to compete, loss of access to financing sources, and failure of MSMEs. A high level of social capital can make it easier for people to work together in related fields and help the MSME sector and business performance.